Prenatal polycyclic aromatic hydrocarbon (PAH) exposure in relation to placental corticotropin releasing hormone (pCRH) in the CANDLE pregnancy cohort - Barrett, Emily S.; Workman, Tomomi; Hazlehurst, Marnie F.; Kauderer, Sophie; Loftus, Christine; Kannan, Kurunthachalam; Robinson, Morgan; Smith, Alicia K.; Smith, Roger; Zhao, Qi; LeWinn, Kaja Z.; Sathyanarayana, Sheela; et al. (Frontiers in Endocrinology, 2022)
Polycyclic aromatic hydrocarbons (PAHs) are ubiquitous endocrine-disrupting combustion by-products that have been linked to preterm birth. One possible mechanism is through disruption of placental corticotropin releasing hormone (pCRH), a key hormone implicated in parturition. As an extension of recent research identifying pCRH as a potential target of endocrine disruption, we examine maternal PAH exposure in relation to pCRH in a large, diverse sample. Participants, drawn from the CANDLE cohort, part of the ECHO-PATHWAYS Consortium, completed study visits at 16-29 weeks (V1) and 22-39 weeks (V2) gestation (n=812). Seven urinary mono-hydroxylated PAH metabolites (OH-PAHs) were measured at V1 and serum pCRH at V1 and V2. Associations between individual log-transformed OH-PAHs (as well as two summed PAH measures) and log(pCRH) (concentrations at each timepoint and the change over time were estimated using linear regression models. Minimally-adjusted models included gestational age and urinary specific gravity, while fully-adjusted models also included sociodemographic characteristics. We additionally evaluated effect modification by pregnancy complications, fetal sex, and maternal childhood trauma history. In minimally-adjusted models, most OH-PAHs were inversely associated with pCRH concentrations. For instance, 1-hydroxypyrene (1-OH-PYR) was associated with lower V1 (β=-0.10, 95%CI: -0.16, -0.03) and V2 (β=-0.08, 95%CI: -0.15, -0.004) log(pCRH). After adjustment for sociodemographic factors, however, results were attenuated and non-significant for all OH-PAHs, including associations between 1-OH-PYR and log(pCRH) at V1 (β=-0.01, 95%CI: -0.07, 0.05) and V2 (β=0.01, 95%CI: -0.07, 0.08). We observed no evidence of effect modification by pregnancy complications, fetal sex, or maternal childhood trauma history. In conclusion, in contrast to the single prior study on this topic, we observed little evidence of association between OH-PAHs and pCRH in this sample, which may be due to differences in pCRH assay methods as well as timing of measurement. Additional research with repeat measures of PAH exposures is warranted, as is investigation of alternative mechanisms that may link PAHs and timing of birth, such as inflammatory, epigenetic, or oxidative stress pathways.